THE EFFECT OF ESG RISK ON FINANCIAL RISK WITH PROFITABILITY AS A MODERATING VARIABLE - Yorilola Yoanda Putri; Ketzia Marylee; Yulius Jogi Christiawan; Hendri Kwistianus (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to examine the influence of ESG Risk and profitability on Financial Risk, in addition, this study also wants to test the role of profitability in moderating the influence of ESG Risk on the Financial Risk of companies on the IDX. This study uses panel data from 57 non-financial companies with ESG scores from 2023 to 2024. ESG risk is measured using the ESG score, profitability using ROA, and financial risk using the inverse of the Bathory Metrics Model (BMM). The study also uses leverage, firm size, and sales growth as control variables. The analysis tool used is Eviews with the Fixed Effects Model (FEM). The research results show that ESG Risk has a negative effect on Financial Risk. This is because companies incur significant short-term costs to meet sustainability requirements in the ESG score assessment, leading to debt financing, which increases financial risk, consistent with the finding that leverage has a positive effect on financial risk. The research also shows that Profitability has no significant effect on Financial Risk and is unable to moderate the effect of ESG Risk on Financial Risk. The use of ESG Scores as a measure of ESG risk is not yet widely practiced in Indonesia, as only a few companies have registered to have their ESG scores assessed. This study also demonstrates a unique finding: higher ESG risk actually leads to lower financial risk, contrasting with much previous literature.